Implementasi Kebijakan Skema Murur dalam Penyelenggaraan Haji: Analisis Manajemen Operasional Berdasarkan Model Van Meter–Van Horn - Islamiyah, Niswatul; Affandi, Yuyun; Rozaq, Abdul; Hilmi, Mustofa; Malik, Hatta Abdul; Kasmuri, Kasmuri (FASTABIQ: JURNAL STUDI ISLAM, 2025)
The implementation of the murur scheme in Muzdalifah emerged as a strategic response of the Indonesian Ministry of Religious Affairs to the extreme crowding observed during the 2023 Hajj season. The scheme allows eligible pilgrims to pass through Muzdalifah without staying overnight after completing wukuf in Arafah, proceeding directly to Mina. Priority is given to elderly pilgrims, individuals with high medical risk, persons with disabilities, those with obesity, wheelchair users, and officially assigned companions. This study aims to examine the operational management of the murur scheme, analyze its policy implementation using the Van Meter and Van Horn framework, and evaluate the effectiveness of its execution. A qualitative research design was employed, utilizing observation, interviews, and document analysis. The findings indicate that the operational management of the murur scheme was sufficiently effective during its inaugural implementation. The Decree of the Director General of Hajj and Umrah Affairs No. 137/2025 further outlines detailed procedures for the 2025 Hajj cycle, covering the Arafah, Muzdalifah, and Mina phases. The study contributes to strengthening operational efficiency, enhancing pilgrim safety, and supporting continuous policy refinement within large-scale Hajj management systems.  Keywords: Murur Scheme; Operational Management; Hajj Performance; Policy Implementation; Van Meter–Van Horn Model